2020
DOI: 10.3390/molecules25051215
|View full text |Cite
|
Sign up to set email alerts
|

The Oxygen Consumption Kinetics of Commercial Oenological Tannins in Model Wine Solution and Chianti Red Wine

Abstract: One property of oenological tannins, oxygen reactivity, is commonly exploited in winemaking. The reactivity is mediated by the presence of catalysts (i.e., transition metals and sulfur dioxide) and protects wine against oxidation. This work compares the oxygen consumption rate (OCR) of four commercial oenological tannins (two procyanidins from grape skin and seed, an ellagitannin from oak wood and a gallotannin from gallnut) in a model wine solution and Chianti red wine. All samples were subjected to consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 53 publications
(59 reference statements)
3
13
0
Order By: Relevance
“…Besides their flavor, which determines their use, wine and beer are known as rich with bioactive compounds, i.e., antioxidants that increase the interest in their nutritional profile. A great number of studies and comprehensive reviews have dealt with the bioactive compounds responsible for the possible health benefits due to moderate wine and beer consumption, and with the different methods of improvement of the antioxidant compounds in these two beverages [3][4][5][6][7][8][9][10][11][12][13][14]. Much of this research supports the thesis that moderate consumption of alcoholic beverages, such are red wine and beer, positively influences the decrease of cardiovascular disease [3].…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Besides their flavor, which determines their use, wine and beer are known as rich with bioactive compounds, i.e., antioxidants that increase the interest in their nutritional profile. A great number of studies and comprehensive reviews have dealt with the bioactive compounds responsible for the possible health benefits due to moderate wine and beer consumption, and with the different methods of improvement of the antioxidant compounds in these two beverages [3][4][5][6][7][8][9][10][11][12][13][14]. Much of this research supports the thesis that moderate consumption of alcoholic beverages, such are red wine and beer, positively influences the decrease of cardiovascular disease [3].…”
Section: Introductionmentioning
confidence: 64%
“…Due to this maceration, occurring along with alcoholic fermentation during red winemaking, in which the phenolic compounds are extracted from grapes, this step represents the key one in determining the content of polyphenolic compounds in red wine. Furthermore, because of this step, it is commonly known that red wine contains more antioxidant compounds, and has been more studied and reviewed by researchers in the last decades [14,[26][27][28][29][30][31][32][33][34]. Another important step during winemaking in which it is possible to increase polyphenolic compounds is ageing in wood barrels, or with addition of oak alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrolyzable tannins, and particularly ellagitannins, are able to regulate oxidation, to quickly react with dissolved oxygen, and to facilitate the hydroperoxidation of wine constituents inducing tannin/anthocyanin condensation, thus enhancing color stabilization and deepening the crimson color [ 12 ]. Ellagitannins have been reported as the most effective oenotannins in protecting wine against chemical oxidation [ 2 , 30 ]. The ellagitannin vescalagin reacts with the red-colored anthocyanin oenin (a grape pigment) to provide a purple-colored anthocyanin-ellagitannin pigment [ 31 ], suggesting the capability of ellagitannins to directly react with anthocyanins.…”
Section: Introductionmentioning
confidence: 99%
“…In model solutions, it was observed that gallotannins have an excellent scavenging capacity while the ellagic improve iron(II) chelation and the condensed tannins have a significant ability to scavenge peroxyl radicals [ 10 ]. Moreover, the addition of ellagitannin in red winemaking operations increased the rate of O 2 consumption [ 11 ]. The consumption of oxygen in wine is strictly related to phenolic compounds which are primary substrates for wine oxidation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%